En konservativ konservering af klimaet? En undersøgelse af konservatismens diskursive, ideologiske og historiske forhold til menneskeskabte klimaforandringer - Hattens, Christian Egholm (Culture and History: Student Research Papers, 2022)
This paper examines the strategy undertaken by the conservative climate sceptic countermovement to counter the scientific consensus on human caused climate change. It focuses on revealing the power of the discursive production of knowledge by conservative actors in spreading misinformation to the media, powerful institutions, and the public. The paper examines the reasons behind this strategy and argues that, apart from economic reasons, both historical and ideological factors within conservatism can help explain this behavior. Lastly, the paper discusses, in a theoretical sense, whether conservatism can ever be reconciled with a conservation of the climate, and, in a practical sense, obstacles, such as climate skeptical discourses, for a conservative pro-climate movement to succeed politically.